Similarities and Differences of Hsp70, hsc70, Grp78 and Mortalin as Cancer Biomarkers and Drug Targets - Rajani Rai; Amy L. Kennedy; Zitha Redempta Isingizwe; Pouya Javadian; Doris Mangiaracina Benbrook (Cells, 2021)
Background: Upregulation of Heath Shock Protein 70 (HSP70) chaperones supports cancer cell survival. Their high homology causes a challenge to differentiate them in experimental or prevention and treatment strategies. The objective of this investigation was to determine similarities and differences of Hsp70, hsc70, Grp78 and Mortalin members of the HSP70 family encoded by HSPA1, HSPA8, HSPA5 and HSPA9 genes, respectively. Methods: Literature reviews were conducted using HSPA1, HSPA5, HSPA8 and HSPA9 gene or protein names or synonyms combined with biological or cancer-relevant terms. Ingenuity Pathway Analysis was used to identify and compare profiles of proteins that directly bind individual chaperones and their associated pathways. TCGA data was probed to identify associations of hsc70 with cancer patient survival. ClinicalTrials.gov was used to identify HSP70 family studies. Results: The chaperones have similar protein folding functions. Their different cellular effects are determined by co-chaperones and client proteins combined with their intra- and extra-cellular localizations. Their upregulation is associated with worse patient prognosis in multiple cancers and can stimulate tumor immune responses or drug resistance. Their inhibition selectively kills cancer over healthy cells. Conclusions: Differences in Hsp70, hsc70, Grp78 and mortalin provide opportunities to calibrate HSP70 inhibitors for individual cancers and combination therapies.